On a new critical point theorem and some applications to discrete equations - Galewski, Marek; Galewska, Elżbieta (AGH University of Science and Technology Press, 2014)
Using the Fenchel-Young duality we derive a new critical point theorem. We illustrate our results with solvability for certain discrete BVP. Multiple solutions are also considered.
Keywords: critical point; multiplicity; discrete equation; Fenchel-Young transform